Current account imbalances in the euro area: Catching up or competitiveness? - Ansgar Belke; Christian Dreger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
In the debate on global imbalances, the euro area countries did not receive much attention so far. While the current account is on balance for the entire area, divergences between individual member states have increased since the introduction of the common currency. In this paper, the imbalances are traced back to catching up and competitiveness factors using paneleconometric techniques. In line with the intertemporal approach to the current account, low income countries tend to run deficits, while rich countries realize surpluses. However, the effect diminishes, if early years are dropped from the sample. The competitiveness channel is more robust and shows the expected sign, i.e. real appreciation leads to external deficits. To restore competitiveness, a reduction of unit labour costs is on the agenda. Since a deterioration of competitiveness is not a feasible strategy for the surplus countries, an asymmetric response across countries is required in order to reduce the imbalances.
Keywords: F32; F36; E44; 330; Current account imbalances; catching up and competitiveness; euro area